Answer :
Answer:
1, 3, 4
Step-by-step explanation:
6x + c = 2(3x + 1) use the distributive property a(b + c) = ab + ac
6x + c = (2)(3x) + (2)(1)
6x + c = 6x + 2 subtract 6x from both sides
6x - 6x + c = 6x - 6x + 2
c = 2
The equation has no solution if we get a false equation without the variable y.
Therefore c ≠ 2.
Answer:
1, 3, 4
Step-by-step explanation:
Given equation,
6x + c = 2(3x + 1),
⇒ 6x + c = 6x + 2 ( By distributive property ),
⇒ c = 2 -----(1) ,
∵ An equation has no solution when after solving the equation we get a false statement,
if c = 1,
From equation (1),
1 = 2 ( False )
⇒ given equation has no solution,
if c = 2,
From equation (1),
2 = 2 ( True )
⇒ the given equation has infinitely many solutions,
if c = 3,
From equation (1),
3 = 2 ( False )
⇒ the given equation has no solution,
if c = 4,
From equation (1),
4 = 2 ( False )
⇒ the given equation has no solutions.